LEKSIKON ETNOMEDISIN PENGOBATAN TRADISIONAL MASYARAKAT MELAYU DESA NANGA DANAU, KABUPATEN KAPUAS HULU: KAJIAN EKOLINGUISTIK - Suryana, Desi Liani; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research examines the ethnomedicine lexicon related to the traditional medicine of the Malay community in Nanga Danau Village. The study aims to identify and describe the forms of lexicons associated with traditional medicine in the village and analyze their lexical, grammatical, and cultural meanings in the Malay language of Nanga Danau Village. Employing a qualitative descriptive method, the study relies on data collected from native speakers of the Kapuas Hulu Malay language who are directly involved in traditional medical practices in the village. The data consists of lexicons related to traditional medicine, focusing on lingual units such as words and phrases, as well as their lexical, grammatical, and cultural meanings. Data collection methods include observation, interviews, recording, note-taking, and translation techniques, utilizing tools such as questionnaires, recording devices, and stationery. The findings reveal 77 lexicons related to traditional medicine in the Malay community of Nanga Danau Village, including 9 lexicons for disease names, 5 for treatment names, 26 for treatment materials, and 37 for treatment methods. The linguistic forms of these lexicons comprise 15 monomorphemic units, 6 polymorphemic units, and 56 phrases. Additionally, 77 lexicons have been identified with lexical meanings.